Sociocultural Perspectives in Exploring Personal Reading Histories for Learners of FKIP University of Riau - Delfi, Syofia; Diah, Fangiana Safitri; Safriyanti, Maria (Proceedings of the UR International Conference on Educational Sciences, 2018)
Becoming interest in reading for EFL learners majoring in English is as the reflection of interaction with others in reading experiences. This article is a critical analysis of related theories for analyzing a study âThe Analysis of Reading Experiences based on Exploring Personal Reading Histories for Learners of FKIP University of Riauâ. This article aims to explore how Sociocultural theory is appropriate in analyzing the learnersâ experiences based on Exploring Personal Reading Histories for the learners of FKIP University of Riau. Critical analysis was conducted in this study. The result of analysis shows that Sociocultural theory is appropriate for learners of FKIP University of Riau in terms of reading experiences of Indonesian learners mediated by language, interact with others, and develop self-regulation in the process for reading competence and reading interest. The finding shows how the concept of mediation, practice, scaffolding, self-direction, and zone of proximal development in Sociocultural theory reflect on the learnersâ reading experiences. The result of the analysis is expected to be meaningful for the study designed.